Peran promosi media sosial dan electronic-word-of-mouth terhadap minat beli produk kuliner - Anis Marjukah; Sarwono Nursito; Rizky Windar Amelia (Jurnal Manajemen Maranatha, 2024)
With technological advancements, economic dynamics are also undergoing changes. The increasing use of social media demands that businesses adapt in order to compete effectively in meeting consumer expectations. For efficiency and effectiveness, promoting through social media has become a necessity. The objective of this research is to determine the impact of social media promotion and electronic word of mouth (e-WOM) on the purchase intention of culinary products. The population for this study comprises customers in Klaten Regency who use social media platforms such as Instagram, TikTok, or YouTube to choose their culinary products. The sample for the study is 110 respondents, selected using purposive sampling technique. Data analysis includes descriptive analysis and multiple linear regression analysis using SPSS software. The results of the study are a) promotions using social media have a positive and significant effect on the purchase intention of culinary products; b) e-WOM has a positive and significant effect on the purchase intention of culinary products; c) promotions using social media and e-WOM have a positive and significant effect on the purchase intention of culinary products simultaneously. Practical implications are culinary product businesses need to design and implement promotional strategies, especially on social media, to expand and encourage e-WOM to increase purchase intention. Limitations of the study are the social media platforms used are limited to only three platforms, namely Instagram, TikTok, or YouTube. Businesses may use other platforms such as Facebook, Snapchat, or Social Blogging Networks as alternative means of promotion.